ASSESMENT OF BUSINESS EFFICIENCY OF AGRICULTURAL HOLDINGS WITH DIFFERENT PRODUCTIONS - Orović, Dragan; Ljubanović Ralević, Ivana; Anokić, Ana (Economics of Agriculture, 2015)
The subject of this paper is the use of DEA methodology for the evaluation and analysis of the total technical effciency (TE) which also includes the pure technical effciency (PTE) and scale effciency (SE). The operations of three groups of 20 individual farms, with different primary production, feld crops, fruit and livestock, are analysed in the present paper. The necessary data for the development of the basic model have been collected by the survey conducted on 60 agricultural households on the territory of Toplice region. Surveyed households have 92 tractors, 108 different ploughs, 63 sprayers and other necessary mechanization. In addition, 677.7 ha of agricultural land, which is located at 1,201 plots, are cultivated by surveyed households. These farms keep 291 cows, 118 bulls, 366 pigs, 459 sheep and others. 91 workers and farm members are engaged in operation of the farms. The aim of the paper is to determine whether there is a difference in the technical effciency of different types of households.